Phục hồi kinh tế do ảnh hưởng của đại dịch COVID-19 – Kinh nghiệm quốc tế và hàm ý chính sách kinh tế vĩ mô cho Việt Nam - Nguyễn Tiến , Dũng; Lê Việt , An (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The COVID-19 pandemic has caused a severe economic crisis worldwide, forcing countries to quickly develop urgent solutions in the style of “doing and fixing.” By using qualitative research methods, this study analyzes and systematizes the fiscal and monetary policies that have been implemented in the 15 countries that are well resilient to the negative impacts of the COVID-19 pandemic, according to the European Investment Bank (EIB). This study also analyzes the current situation of applying fiscal and monetary policies of Vietnam to serve as a basis for making policy suggestions for the Government of Vietnam. Specifically, in terms of fiscal policy, the Government should disburse public spending to focus on critical national projects, technology development, and green economy in the long term. At the same time, it is also necessary to prioritize financial support for subjects and industries that are heavily damaged by the pandemic in the short term. In terms of monetary policy, in the short time, the Government can loosen requirements on credit risk management at commercial banks, accelerate the implementation of e-banking services and develop FinTech in the long term.